The development of chronic pain: physiological CHANGE necessitates a multidisciplinary approach to treatment. (September 2013) - Pergolizzi, Joseph; Ahlbeck, Karsten; Aldington, Dominic; Alon, Eli; Coluzzi, Flaminia; Dahan, Albert; Huygen, Frank; Kocot-Kępska, Magdalena; Mangas, Ana Cristina; Mavrocordatos, Philippe; Morlion, Bart; Müller-Schwefe, Gerhard; et al.
Abstract Chronic pain is currently under-diagnosed and under-treated, partly because doctors' training in pain management is often inadequate. This situation looks certain to become worse with the rapidly increasing elderly population unless there is a wider adoption of best pain management practice. This paper reviews current knowledge of the development of chronic pain and the multidisciplinary team approach to pain therapy. The individual topics covered include nociceptive and neuropathic pain, peripheral sensitization, central sensitization, the definition and diagnosis of chronic pain, the biopsychosocial model of pain and the multidisciplinary approach to pain management. This last section includes an example of the implementation of a multidisciplinary approach in Belgium and describes the various benefits it offers; for example, the early multidimensional diagnosis of chronic pain and rapid initiation of evidence-based therapy based on an individual treatment plan. The patient also receives continuity of care, while pain relief is accompanied by improvements in physical functioning, quality of life and emotional stress. Other benefits include decreases in catastrophizing, self-reported patient disability, and depression. Improved training in pain management is clearly needed, starting with the undergraduate medical curriculum, and this review is intended to encourage further study by those who manage patients with chronic pain.